Perlindungan Hukum Wilayah Pesisir dalam Pengendalian Pencemaran dan Perusakan Laut Pesisir di Negeri Batumerah Damer, Kabupaten Maluku Barat Daya - Tomy Palijama; Sintia Elisabeth Renyut (Balobe Law Journal, 2021)
Introduction: Indonesia with its geographic form as an archipelagic country. Based on these considerations, the Indonesian government states that all waters around, between and connecting islands are the territorial territory of the Indonesian state. Purposes of the Research: Assessing and analyzing the legal protection of coastal areas in controlling pollution and destruction of coastal seas.Methods of the Research: This research is a normative study using a statutory approach with the source of legal materials used  primary legal materials and secondary legal materials and tertiary legal materials with qualitative analysis with deductive and inductive methods. Results of the Research: Environmental pollution is caused by human activities themselves, either through industrial activities or household activities that produce waste and garbage, which are grouped into 3 things, namely the existence of environmental pollution (pollution), land misuse (land misused) and destruction or depletion of sources. natural resources (Natural Resources). Environmental pollution in the form of water pollution which includes rivers and lakes, marine pollution, air pollution and noise.